Economic Impact of Revision Operations for Adjacent Segment Disease of the Subaxial Cervical Spine. (21st April 2022) - Bonano, John; Cummins, Daniel D.; Burch, Shane; Berven, Sigurd H.; Deviren, Vedat; Ames, Christopher P.; Tay, Bobby; Clark, Aaron J.; Theologis, Alekos A.
Abstract : Introduction: Adjacent segment disease (ASD) of the cervical spine is a common disabling phenomenon that often requires surgical intervention. The goal of this study was to evaluate the economic impact of revision operations for cervical ASD. Methods: Consecutive adults who underwent revision cervical spine surgery for ASD at a single institution between 2014 and 2017 were retrospectively reviewed. Direct costs were identified from medical billing data and calculated for each revision surgery for ASD. Incomplete cost data for revision operations were used as a criterion for exclusion. Cost data were stratified based on the approach of the index and revision operations. Results: Eighty-five patients (average age 57 ± 10 years) underwent revisions for cervical ASD, which summed to 2 million (average 23, 702). Revisions consisted of 45 anterior operations (anterior cervical diskectomy and fusion, 34; corpectomy, 10; and cervical disk arthroplasty, 1), 32 posterior operations (posterior cervical fusion, 14; foraminotomy, 14; and laminoplasty, 4), and 8 circumferential operations. Circumferential revisions had notably higher average direct costs (57, 376) than single approaches (anterior, 20, 084 and posterior, 20, 371). Of posterior revisions, foraminotomies had the lowest average direct costs (5, 389), whereas posterior cervical fusion had the highest average direct costs (35, 950). Of anterior revisions, corpectomies (30, 265) had notably greater average direct costs than anterior cervical diskectomy and fusion (17, 514). Costs were not notably different for revision approaches based on the index operations' approach. Discussion: Revision operations for cervical ASD are highly heterogeneous and associated with an average direct cost of 27, 702. Over 3 years, revisions for 85 patients with cervical ASD represented a notable economic expense (greater than 2.0 million). Data availability: Deidentified data may be provided by request to the corresponding author.